PERAMALAN CONSTRUCTION COST INDEX (CCI) DI INDONESIA MENGGUNAKAN MODEL SEASONAL ARIMA - Indriyani, Armelia; Nanda Azzanina (Yayasan Nusantara Hasana Berdikari, 2026)
The construction sector is a crucial pillar of Indonesia's economic development, reflected in its contribution to Gross Domestic Product (GDP). The Construction Cost Index (CCI) is closely related to this sector as an indicator of changes in construction costs over time. Fluctuations in the CCI, influenced by trends, seasonal patterns, and external factors, pose challenges in project cost planning, necessitating an accurate forecasting method. This study applies the Seasonal Autoregressive Integrated Moving Average (SARIMA) to forecast the quarterly CCI for the period 2010–2024, as published by Badan Pusat Statistik (BPS). The analysis includes stationarity testing, model identification using ACF and PACF, parameter estimation, diagnostic testing, and model selection based on MAPE. The best model is with a MAPE of less than 10%, indicating excellent accuracy. The results are expected to serve as a reference for cost planning and risk reserves for construction projects in Indonesia.